1992
DOI: 10.1017/s0016756800008128
|View full text |Cite
|
Sign up to set email alerts
|

The margin of a Middle Pleistocene ice advance at Tottenhill, Norfolk, England

Abstract: Exposures at Tottenhill quarry, west Norfolk, are described. Detailed sediment logs, lateral sediment distribution and facies relationships are presented, together with palaeocurrent measurements and pebble counts. It is concluded that the sequence represents a delta-like subaquatic fan accumulation that was deposited by glacier meltwater at the eastern margin of the present Fenland. The ice must have entered the area from the west to northwest. An arctic leaf flora is associated with still water pool sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
76
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 20 publications
10
76
0
1
Order By: Relevance
“…The same programme of geological mapping also concluded that a MIS 6 glaciation reached the north coast of East Anglia where it deposited a distinctive lithofacies with Scandinavian erratics and produced distinctive ice marginal landforms such as push-moraines and outwash fans with ice-contact slopes, similar to those formed during MIS 6 glaciations further east in the Netherlands and north Germany (Hamblin et al, 2000;, Rose 2009). This ice limit is linked to a proposal for a MIS 6 glaciation identified by outwash sediments in northwest Norfolk (Gibbard et al, 1992Gibbard and Clark, 2011). The age for this glacial event is based palaeosol microstratigraphy from an overlying fossil soil (Lewis and Rose, 1999)) and the freshness of the topography by comparison with northern Europe.…”
Section: Late Middle Pleistocene Glaciations (Mis 12-6)mentioning
confidence: 85%
See 1 more Smart Citation
“…The same programme of geological mapping also concluded that a MIS 6 glaciation reached the north coast of East Anglia where it deposited a distinctive lithofacies with Scandinavian erratics and produced distinctive ice marginal landforms such as push-moraines and outwash fans with ice-contact slopes, similar to those formed during MIS 6 glaciations further east in the Netherlands and north Germany (Hamblin et al, 2000;, Rose 2009). This ice limit is linked to a proposal for a MIS 6 glaciation identified by outwash sediments in northwest Norfolk (Gibbard et al, 1992Gibbard and Clark, 2011). The age for this glacial event is based palaeosol microstratigraphy from an overlying fossil soil (Lewis and Rose, 1999)) and the freshness of the topography by comparison with northern Europe.…”
Section: Late Middle Pleistocene Glaciations (Mis 12-6)mentioning
confidence: 85%
“…[Pre-proof accepted manuscript] 20 distinctive lithofacies with Scandinavian erratics and produced distinctive ice marginal landforms such as push-moraines and outwash fans with ice-contact slopes, similar to those formed during MIS 6 glaciations further east in the Netherlands and north Germany (Hamblin et al, 2000;, Rose 2009). This ice limit is linked to a proposal for a MIS 6 glaciation identified by outwash sediments in northwest Norfolk (Gibbard et al, 1992 Gibbard and Clark, 2011 (1986). Subsequently this ice limit has been moved southward to accommodate the evidence from northwest Norfolk and this new limit is used in Gibbard and Clark (2012).…”
mentioning
confidence: 84%
“…These consist of: (1) a two-stage scheme with glaciation occurring during the Anglian and Wolstonian stages (Baden-Powell, 1948;West and Donner, 1956;Mitchell et al, 1973;Gibbard et al, 1992;Banham et al, 2001); (2) a single-stage scheme with extensive glaciation occurring during the Anglian Stage (MIS 12) (Perrin et al, 1979;Banham, 1988;Hart and Boulton, 1991;Lunkka, 1994); and (3) a multiple-stage scheme with glacial advances occurring in several Middle Pleistocene cold stages Clark et al, 2004;Lee et al, 2004a). The last of these schemes (Table 1) is based upon recognition of several lithologically distinct till sheets in northeast Norfolk, separated by glacial retreat sediments and which are interpreted to reflect glacier advances during eccentricityforced climate cooling.…”
Section: Discussion Of Chronological Significancementioning
confidence: 99%
“…Indirect evidence for glaciation in west Norfolk within the low-lying Fenland basin during MIS 6 is represented by glacial outwash sediments at Tottenhill (Gibbard et al, 1992). These outwash deposits overlie an interglacial peat within the Nar Valley Clay Formation which has been dated by U-series to 317 ± 14 ka BP, equivalent to MIS 9 (Rowe et al, 1997).…”
Section: Discussion Of Chronological Significancementioning
confidence: 99%
See 1 more Smart Citation